Assessment of the challenges faced by the learners in mastering ndebele proverbs in Insiza District. - Moyo, Musa (Midlands State University, 2020)
Mastering of the Ndebele proverbs in Insiza District is influenced by the multi-language societies in Insiza District .The researcher focused on the assessment of challenges faced by learners in mastering the Ndebele proverbs in Insiza District in Matabeleland South Province of Zimbabwe . The target population comprised of teachers, teachers in charge , deputy heads and heads of the schools . Thirty seven questionnaires were distributed to teachers , 3 questionnaire were distributed to teachers in charge and 3 interviews were administered to deputy heads and 3 interviews were administered to the heads of the schools .Data was gathered from both primary and secondary sources . The research findings revealed that the main benefit of the Ndebele proverbs was that they helped enrich the Ndebele language. The study also revealed that the main cause for the failure of learners to master Ndebele proverbs was as a result of the multi-cultural and language societies .The study indicated that the main challenge which was faced by learners in mastering Ndebele proverbs was that the learners spoke different languages . It was also revealed in the study that the main strategy in place to ensure that learners master the Ndebele proverbs were laws supporting the use of the Ndebele language and proverbs .The study recommended that policy makers should come up with a clear language policy that supports indigenous languages . Further study should be done on the effectiveness of the strategies being put in place to ensure that learners master the Ndebele proverbs.